Strike‐Slip Enables Subduction Initiation Beneath a Failed Rift: New Seismic Constraints From Puysegur Margin, New Zealand. Issue 5 (6th May 2021) - Shuck, Brandon; Van Avendonk, Harm; Gulick, Sean P. S.; Gurnis, Michael; Sutherland, Rupert; Stock, Joann; Patel, Jiten; Hightower, Erin; Saustrup, Steffen; Hess, Thomas
Abstract: Subduction initiation often takes advantage of previously weakened lithosphere and may preferentially nucleate along pre‐existing plate boundaries. To evaluate how past tectonic regimes and inherited lithospheric structure might lead to self‐sustaining subduction, we present an analysis of the Puysegur Trench, a young subduction zone with a rapidly evolving tectonic history. The Puysegur margin, south of New Zealand, has experienced a transformation from rifting to seafloor spreading to strike‐slip, and most recently to incipient subduction, all in the last ∼45 million years. Here we present deep‐penetrating multichannel reflection and ocean‐bottom seismometer tomographic images to document crustal structures along the margin. Our images reveal that the overriding Pacific Plate beneath the Solander Basin contains stretched continental crust with magmatic intrusions, which formed from Eocene‐Oligocene rifting between the Campbell and Challenger plateaus. Rifting was more advanced to the south, yet never proceeded to breakup and seafloor spreading in the Solander Basin as previously thought. Subsequent strike‐slip deformation translated continental crust northward causing an oblique collisional zone, with trailing ∼10 Myr old oceanic lithosphere. Incipient subduction transpired as oceanic lithosphere from the south forcibly underthrust the continent‐collision zone. We suggest that subduction initiation at the Puysegur Trench was assisted by inherited buoyancy contrasts and structural weaknesses that were imprinted into the lithosphere during earlier phases of continental rifting and strike‐slip along the plate boundary. The Puysegur margin demonstrates that forced nucleation along a strike‐slip boundary is a viable subduction initiation scenario and should be considered throughout Earth's history. Plain Language Summary: Subduction zones, where one plate underthrusts another, are the principal driver of tectonic plate motions on Earth; however, the origin of these convergent margins remains unsolved. Geoscientists have proposed that the process of forming a new subduction zone takes advantage of weaknesses such as buoyancy contrasts and re‐using older weak plate boundaries. To test these ideas, we use new seismic images to document tectonic structures at the Puysegur margin, an incipient subduction zone south of New Zealand. Our images reveal that the upper plate of the Puysegur margin consists mostly of stretched continental lithosphere that formed during an Eocene‐Oligocene extension phase. Following extension, a translational phase juxtaposed thin and high‐density oceanic lithosphere against thick and low‐density continental lithosphere in a wide damage zone. Convergence across this zone led to underthrusting of the Australian Plate beneath the Pacific Plate and the development of the newly established Puysegur subduction zone. Our results demonstrate that subduction initiation was aided by lithospheric buoyancy contrasts and weak zones inherited from earlier phases of tectonic activity. Our findings argue that pre‐existing plate boundaries, weakening mechanisms, and strike‐slip are key components of the subduction initiation process and have likely prevailed throughout Earth's history. Key Points: Deep‐penetrating seismic velocity and reflection images provide constraints on regional crustal structure of an incipient subduction zone Earlier phases of continental rifting, seafloor spreading, and strike‐slip produced weaknesses that facilitated subduction initiation Subduction nucleated at a restraining bend as ∼10 Myr thin and dense oceanic lithosphere underthrusted buoyant continental lithosphere